2021
DOI: 10.3389/fnint.2021.685627
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating the Minimal Number of Repeated Examinations for Random Responsiveness With the Coma Recovery Scale—Revised as an Example

Abstract: Objective: The aim of this study was to develop a general method to estimate the minimal number of repeated examinations needed to detect patients with random responsiveness, given a limited rate of missed diagnosis.Methods: Basic statistical theory was applied to develop the method. As an application, 100 patients with disorders of consciousness (DOC) were assessed with the Coma Recovery Scale–Revised (CRS-R). DOC patients were supposed to be examined for 13 times over 20 days, while anyone who was diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Collective evidence evaluating the utility of the CRS-R, compared to other behavior rating scales, diagnostic modalities, and neurophysiological studies, demonstrates the superiority of the CRS-R as a sensitive and reliable tool to accurately identify and discriminate among the levels of DoC ( Lechinger et al, 2013 ; Annen et al, 2019 ; Formisano et al, 2019a ; da Conceição Teixeira et al, 2021 ). Additional evidence focusing on the utility of the CRS-R identifies the benefit of serial use of the CRS-R to improve accuracy of identifying behavioral presentation of DoC ( Wannez et al, 2017 ; Yang et al, 2021 ). Further evaluation and investigation of the CRS-R has produced development of a CRS-R index to improve total score interpretation and translation of the CRS-R into multiple languages for international use ( Lombardi et al, 2007 ; Tamashiro et al, 2014 ; Binder et al, 2018 ; Annen et al, 2019 ; Zhang et al, 2019 ).…”
Section: Overview Of Standardized Neurobehavioral Assessments For Docmentioning
confidence: 99%
See 2 more Smart Citations
“…Collective evidence evaluating the utility of the CRS-R, compared to other behavior rating scales, diagnostic modalities, and neurophysiological studies, demonstrates the superiority of the CRS-R as a sensitive and reliable tool to accurately identify and discriminate among the levels of DoC ( Lechinger et al, 2013 ; Annen et al, 2019 ; Formisano et al, 2019a ; da Conceição Teixeira et al, 2021 ). Additional evidence focusing on the utility of the CRS-R identifies the benefit of serial use of the CRS-R to improve accuracy of identifying behavioral presentation of DoC ( Wannez et al, 2017 ; Yang et al, 2021 ). Further evaluation and investigation of the CRS-R has produced development of a CRS-R index to improve total score interpretation and translation of the CRS-R into multiple languages for international use ( Lombardi et al, 2007 ; Tamashiro et al, 2014 ; Binder et al, 2018 ; Annen et al, 2019 ; Zhang et al, 2019 ).…”
Section: Overview Of Standardized Neurobehavioral Assessments For Docmentioning
confidence: 99%
“…Based on these results, the authors recommend performing at least five assessments within a short time interval (e.g., 2 weeks) to boost diagnostic certainty, even in persons with chronic DoC ( Wannez et al, 2017 ). A similar study by Yang et al (2021) developed statistical formulas to estimate the probability of positive response with use of the CRS-R in relation to the minimal number of successive examinations. Yang et al (2021) identified that a minimum of five assessments is needed for patients with non-traumatic DoC and six assessments for traumatic DoC ( Yang et al, 2021 ).…”
Section: Practical Strategies For Optimizing Neurobehavioral Assessme...mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Instead, five or more assessments repeated over several days may be necessary to appropriately evaluate the level of consciousness in patients with prolonged disorders of consciousness (36% misdiagnosis with a single assessment vs. 5% with five assessments). 69 70…”
Section: Mcs and Emerged From Mcsmentioning
confidence: 99%
“…15 Instead, five or more assessments repeated over several days may be necessary to appropriately evaluate the level of consciousness in patients with prolonged disorders of consciousness (36% misdiagnosis with a single assessment vs. 5% with five assessments). 69,70 The MCS is frequently a transitional state, as patients who were previously comatose or VS/UWS improve to MCS during their recovery trajectory. A transition from MCS to a higher plane of consciousness or better is signaled when patients demonstrate reliable functional communication, or the ability to use two different objects appropriately, or both; such patients are designated as "emerged from MCS" (eMCS).…”
Section: Mcs and Emerged From Mcsmentioning
confidence: 99%